2021
DOI: 10.1177/03635465211041381
|View full text |Cite
|
Sign up to set email alerts
|

Increased Shoulder Distraction Force and Shoulder Horizontal Abduction in Professional Baseball Pitchers With Discordant Torso Rotation Order

Abstract: Background: Inefficient energy transfer from the pelvis and trunk has been shown to increase compensation at the level of the shoulder. Kinetic chain sequencing of the core segments is underexamined in professional baseball pitchers, especially as it relates to changes in upper extremity kinetics. Purpose: To evaluate elbow and shoulder kinetics in a cohort of professional pitchers differentiated by instances of discordant pelvic to upper torso sequencing during the pitch. Study Design: Descriptive laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In particular, professional and high school pitchers with increased forearm pronation at the individual level had decreased elbow flexion and shoulder external rotation at FC, while achieving maximum elbow extension velocity later in the pitch. These are important findings given that increased elbow flexion, 16 shoulder external rotation, 18 and improper timing of maximum segmental joint velocities 17 , 19 , 24 , 30 have all been studied previously and implicated in increased throwing arm kinetics or injury risk. Though these parameters were evaluated during later portions of the pitch (ie, maximum shoulder external rotation, ball release), the means by which one kinematic may influence subsequent portions of the pitching motion is important in elucidating combinatory sequences that may pose the highest injury risk to pitchers and warrants further investigation.…”
Section: Discussionmentioning
confidence: 71%
“…In particular, professional and high school pitchers with increased forearm pronation at the individual level had decreased elbow flexion and shoulder external rotation at FC, while achieving maximum elbow extension velocity later in the pitch. These are important findings given that increased elbow flexion, 16 shoulder external rotation, 18 and improper timing of maximum segmental joint velocities 17 , 19 , 24 , 30 have all been studied previously and implicated in increased throwing arm kinetics or injury risk. Though these parameters were evaluated during later portions of the pitch (ie, maximum shoulder external rotation, ball release), the means by which one kinematic may influence subsequent portions of the pitching motion is important in elucidating combinatory sequences that may pose the highest injury risk to pitchers and warrants further investigation.…”
Section: Discussionmentioning
confidence: 71%
“…Likewise, the lack of sagittal plane differences observed in this study may also be related to similar pitching ability among the pain and pain-free groups as indicated by similar pitch speeds. 25 Therefore, differences in pelvic and trunk mechanics may be linked more to performance/velocity than the result of arm pain. Future biomechanical research comparing pain and pain-free groups of pitchers should include subgrouping locations of pain, longitudinally collected data such as changes in player demographics, pitching workloads, pitch types, variance in kinematics, and mechanical variables of the throwing arm in addition to the variables used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…13 Therefore, a comparison study between pain and pain-free groups of pitchers using time-series data may be useful in detecting mechanical differences and for examining kinematic patterns that may be associated with pain. 6,15,25,28 Although research has identified pitching-related injury risk factors in youth baseball players, 12,22,23,29,30,35 the factors associated with these injuries, specifically trunk and pelvic kinematics when throwing with pain, are not well understood. 14,18,42 An improved understanding of trunk and pelvic mechanics during the pitching motion associated with UE pain in youth baseball pitchers would be beneficial in determining modifiable-risk factors in youth pitchers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pitch efficiency is an emerging metric used to quantify efficient mechanics. 1,5,7,13,14 However, this term is already commonly used in baseball parlance to describe throwing the fewest number of pitches per inning. To eliminate confusion, we have chosen to use the phrase ''biomechanical efficiency'' to denote an optimized delivery.…”
mentioning
confidence: 99%